2018
DOI: 10.1016/j.ebiom.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Clock Regulates Metabolic Phenotype Rewiring Via HKDC1 and Modulates Tumor Progression and Drug Response in Colorectal Cancer

Abstract: An endogenous molecular clockwork drives various cellular pathways including metabolism and the cell cycle. Its dysregulation is able to prompt pathological phenotypes including cancer. Besides dramatic metabolic alterations, cancer cells display severe changes in the clock phenotype with likely consequences in tumor progression and treatment response. In this study, we use a comprehensive systems-driven approach to investigate the effect of clock disruption on metabolic pathways and its impact on drug respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 64 publications
10
100
0
Order By: Relevance
“…Circadian studies have been performed in a multitude of in vitro cell models, ranging from rodent and human immortalized cell lines,such as NIH/3T3‐immortalized mouse embryo fibroblasts (Akashi & Nishida, ) and rat‐1 fibroblasts (Balsalobre, Damiola, & Schibler, ; Izumo, Sato, Straume, & Johnson, ), or human cancer lines, as U2OS osteosarcoma cells (Relógio et al, ); primary cultures, as mouse neonatal cardiomyocytes (du Pré et al, ) and human fibroblasts (Brown et al, ), blood monocytes (Keller et al, ), hair follicle cells (Akashi et al, ), or keratinocytes (Sandu et al, ); to organoids (Fuhr et al, ) and tissue explants, as mouse fetal adrenal gland (Ungar & Halberg, ) or SCN explants (Hughes et al, ).…”
Section: Evaluation Of Circadian Rhythms: From Cells To Humansmentioning
confidence: 99%
See 3 more Smart Citations
“…Circadian studies have been performed in a multitude of in vitro cell models, ranging from rodent and human immortalized cell lines,such as NIH/3T3‐immortalized mouse embryo fibroblasts (Akashi & Nishida, ) and rat‐1 fibroblasts (Balsalobre, Damiola, & Schibler, ; Izumo, Sato, Straume, & Johnson, ), or human cancer lines, as U2OS osteosarcoma cells (Relógio et al, ); primary cultures, as mouse neonatal cardiomyocytes (du Pré et al, ) and human fibroblasts (Brown et al, ), blood monocytes (Keller et al, ), hair follicle cells (Akashi et al, ), or keratinocytes (Sandu et al, ); to organoids (Fuhr et al, ) and tissue explants, as mouse fetal adrenal gland (Ungar & Halberg, ) or SCN explants (Hughes et al, ).…”
Section: Evaluation Of Circadian Rhythms: From Cells To Humansmentioning
confidence: 99%
“…Technological advances have allowed longitudinal measurements in real‐time living cells with a higher temporal resolution, allowing assessment of the persistence and dynamics of molecular rhythms. Automated luminometer devices with photomultiplier tubes, as LumiCycle, are commonly used for real‐time recording (Fuhr et al, ). These systems employ photomultiplier tubes as light detectors, providing extremely high sensitivity and low‐noise data, particularly suitable for data acquisition of extremely dim luc‐based bioluminescence (Ramanathan et al, ).…”
Section: Evaluation Of Circadian Rhythms: From Cells To Humansmentioning
confidence: 99%
See 2 more Smart Citations
“…Fuhr et al recently found that 16.0% (3,998) of all genes were oscillating in SW480 colon cancer cells and 14.8% (3,693) were oscillating in its metastatic counterpart, SW620. However, only 5.5% (1,385) of all genes oscillate in both cell lines, which point to a switch in the 24 h oscillating gene expression profile as cells progress from primary tumour to metastatic .…”
Section: Circadian Rhythm Disruption In Cancermentioning
confidence: 95%